Temperature field evolution and thermal-mechanical interaction induced damage in drilling of thermoplastic CF/PEKK – A comparative study with thermoset CF/epoxy. (24th February 2023) - Ge, Jia; Luo, Ming; Zhang, Dinghua; Catalanotti, Giuseppe; Falzon, Brian G.; McClelland, John; Higgins, Colm; Jin, Yan; Sun, Dan
Abstract: Although new generation carbon fibre reinforced thermoplastic (CFRTP) such as carbon fibre reinforced polyetherketoneketone (CF/PEKK) is a promising sustainable alternative to the conventional thermoset carbon fibre reinforced plastic (CFRP), there is a lack of literature regarding its machining performance. This is the first study unveiling the machining temperature evolution during drilling of CF/PEKK and its potential impact on the associated material damages. Through a comparative study with the thermoset CF/epoxy, the disparate drilling performance of the two composites has been uncovered, and the results were found to be closely related to the materials' thermal/mechanical properties. Specifically, CF/PEKK produces continuous chips due to its excellent ductility and thermal sensitivity, whereas CF/epoxy produces segmented chips due to its brittle nature. CF/PEKK generates up to 40 N (50.5 %) higher thrust force, 87.6 °C (98.9 %) higher hole wall temperature and 61.1 °C (48.8 %) higher chip temperature than that of CF/epoxy. This has been correlated to the longer tool-chip contact length of CF/PEKK and its unique chip morphology. Despite the greater thrust force/temperature generation, CF/PEKK shows 55.7 % lower delamination damage as compared to CF/epoxy, and this is owning to its excellent interlaminar toughness. This study establishes a more in-depth understanding into the drilling performance of thermoplastic CF/PEKK and thermoset CF/epoxy and also provides guidance on the high performance manufacturing of next generation composites. Highlights: The first comparative study on drilling of thermoplastic CF/PEKK and thermoset CFRP Combined thrust force/temperature measurements uncover the thermo-mechanical interaction process during drilling. Disparate composite thermal/mechanical properties lead to different delamination damage. Material removal mechanisms revealed through chip and hole wall microstructural analysis.